ANTASEDEN EMPLOYEE ENGAGEMENT: STUDI KASUS : PERUSAHAAN JASA LAYANAN PELABUHAN (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2017)
The aims of this study were to describe and analyse the influence of organizational culture to employee engagement; to describe and analyse the influence of work environment to employee engagement; to describe and analyse the influence of organizational cultural and work environment to employee engagement as simultaneously. The hyphothesis of this study were: (i) organizational culture and work environmrnt have positiveand and significant influence to employee engagement as partially, and (ii) organizational culture and work environment have positive and significant influence to employee engagement as simultaneously. This study was a causal research to obtain evidences of causal relationships. The technique sampling applied was a cluster random sampling method with questionnaires as the instrument to collect data whose result processed using method Scala Likert Summated Rating (LSR) with score 1 – 4. Respondents of this research were employees of PT Krakatau Bandar Samudera (KBS) – a port services company in the Province of Banten. Respondents of 155 employees were interviewed based on statements in the quetionnaires. This research used technique of path analysis using SPSS software version 22. The results of this hypothesis indicated that (i) organizational culture and work environment have positive and significant influence on employee engagemen as partially, and (ii organizational culture and work environment have positive and significant influence on employee engagement as simultaneously.